Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.1186/s12890-022-02229-y
|View full text |Cite
|
Sign up to set email alerts
|

Application of plasma donor-derived cell free DNA for lung allograft rejection diagnosis in lung transplant recipients

Abstract: Background Donor-derived cell-free DNA (dd-cfDNA) has been applied to monitor acute rejection (AR) in kidney and heart transplantation. This study was aimed to investigate the application of dd-cfDNA levels in the diagnosis of AR and chronic lung allograft dysfunction (CLAD) among the lung transplantation recipients (LTRs). Methods One hundred and seventy LTRs were enrolled at the First Affiliated Hospital of Guangzhou Medical University between 1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 39 publications
(46 reference statements)
1
6
0
Order By: Relevance
“…Elevated plasma dd-cfDNA levels in the rejection group are consistent with previous findings [ 7 , 11 ]. However, dd-cfDNA levels were also found to be slightly elevated in the infection group, especially in cases of CMV infection.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Elevated plasma dd-cfDNA levels in the rejection group are consistent with previous findings [ 7 , 11 ]. However, dd-cfDNA levels were also found to be slightly elevated in the infection group, especially in cases of CMV infection.…”
Section: Discussionsupporting
confidence: 92%
“…In our previous study, we explored plasma dd-cfDNA levels and lung allograft rejection in Chinese LTRs, and our preliminary results suggest that elevated dd-cfDNA levels could be a promising tool for diagnosing rejection in lung transplantation [ 11 ]. Generally, lung allograft rejection should be differentiated from infection, with a negative pathogen result being required.…”
Section: Introductionmentioning
confidence: 99%
“…After a careful review of the titles and abstracts, 304 articles were excluded for duplicate and irrelevance, of which 61 articles were selected for additional screening based on the full text. Finally, a total of 16 studies were included in this systematic review and meta-analysis ( 19 34 ).…”
Section: Resultsmentioning
confidence: 99%
“…A summary of characteristics of the included studies was shown in Tables 1 , Table 2 . Eleven studies were from USA ( 21 , 23 28 , 31 36 ), 1 study from France ( 20 ), 1 study from Italy ( 22 ), and 1 study from Japan ( 29 ), and two studies from China ( 19 , 30 ). In total, eleven studies measured dd-cfDNA levels in graft rejection ( 19 , 21 , 22 , 25 , 26 , 28 – 30 , 32 , 34 ), 6 studies measured dd-cfDNA levels in ACR ( 23 25 , 27 , 31 , 33 ), and 7 studies measured dd-cfDNA levels in AMR ( 21 , 23 25 , 31 , 33 , 34 ), respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation